The combine synergies between Islamic Micro Finance Portfolio and various Structured Finance Solutions - Malik Shahzad Shabbir (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2018)
AbstractPurpose: The objective of this study is to combine the both Islamic micro finance portfolio and structured finance within the limits of Shariah. However, sustainability and access to traditional funding sources by micro finance institutions (MFI) have remained a pressing issue for the finance industry. The traditional sources of finance such as commercial banks have been unwilling and reluctant to join hands with micro finance institutions.Design/methodology/approach A unique structured proposal for business model is suggested in this paper. It combines synergies of structured finance solution for Islamic banks to join hands with existing micro finance providers. The proposed business model will enhance the financing capacity of the existing micro finance Industry by a staggering two thirds, simply by bringing in matching funds from traditional sources. These funds are based on the strong business model using synergies and financially innovative structured solution proposed for risk management etc.Finding It is a commercially viable solution which is capable of being replicated for the entire industry with a huge win-win for all. The results reveal that helping hands for relief development (HHRD) would be providing its share of Rs.115 Million (1045454.54 US dollars) to be matched on 60:40 ratios with Meezan Bank Limited (MBL). Furthermore, Rs.76.667 Million (696972.72 US dollars) and the total Rs.191.667 Million (1742427.27 US dollars) have matched on 30:70 bases between both HHRD and MBL regarding challenges of financial innovation.Originality/valueThis study highlights the issue, why financial institutions of Pakistan especially government sector banks avoided to joint hands with micro finance providers for various reason. These reasons are discussed in detail with proper solution in the paper.